Getúlio Vargas and the national development - Mendes, Rogério Baptistini (Universidade Estadual Paulista / UNESP, 2007)
This article is a result of a research, financed by Fapesp, made as part of the obtention of the degree of Doctor in Sociology. It tries to analyze the relation between president Getúlio Vargas, since his ascension to power in November of 1930, and the ambiguous process of economic, social and political development that followed, resulting in the country's industrialization and in the construction of modern Brazil.